Road ecology impact on capybara species: Operational traffic events involving capybaras (Hydrochoerus hydrochaeris) on the western section of highway in Brazil - G.C.F. Ramos; M.J. Araújo; M. Marinho (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT Capybaras can cause serious traffic accidents, generally resulting in the death of the animal. The objective of this study was to verify the occurrence of accidents expressed as a heat map and propose mitigation measures. The data analyzed comprised a concessioned stretch of highway in the west zone of the state of São Paulo, between January 2019 and December 2020. The parametric data were analyzed using the One-Way ANOVA test and T test. Hotspot maps and Kernel density were done using QGIS 3.20 software. The 946 capybaras were involved in road accidents during this period and, of these, 623 were removed from the highway and 323 died in the accidents. Ten hot spots were found, all concentrated in points with human interference, pointing to the need for mitigating measures